Accelerated Phase Chronic Myeloid Leukemia and Treatment Free Remission Maintained After Five Years of Nilotinib: A Case Report - Capodanno, Isabella; Lugli, Elisabetta; Codeluppi, Katia; Faruolo, Mariapina; Bellesia, Enrica; Valli, Riccardo; Merli, Francesco (Frontiers in Oncology, 2021)
The present article reports the case of a patient presenting with chronic myeloid leukemia, diagnosed during the accelerated phase (>20% blasts in peripheral blood samples and megakaryocytes agglomerates in the bone marrow). The subject was treated in first-line therapy with the tyrosine kinase inhibitor nilotinib and reached complete clinical and molecular remission (according to the European Leukemia Net-ELN-criteria), which persisted over five years of treatment. Five years of discontinuation of nlotinib (ten years from diagnosis), the patient is in good clinical condition, with no traces of BCL-ABL1 at molecular evaluation (molecular response, MR5). The case is discussed in the setting of current literature, providing an overview on chronic myeloid leukemia and a discussion on treatment options available.